The Values of Local Wisdom in Islamic Education at Pesantren Tebuireng - Jasminto, Jasminto (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2024)
This article examines the integration of local wisdom values in Islamic education at Pesantren Tebuireng as an effort to build social harmony, using Pierre Bourdieu's Theory of Cultural Socialization as an analytical framework. Bourdieu emphasizes that educational institutions, such as pesantren, play a crucial role in the reproduction and preservation of culture through habitus, which refers to patterns of thinking, acting, and feeling shaped by the social environment. This study explores how Pesantren Tebuireng implements local values such as tolerance, mutual cooperation, and respect for cultural diversity in its educational process, and how these values are reproduced and preserved in the daily lives of the students. The philosophy of education at Pesantren Tebuireng, influenced by the thoughts of Hadratussyaikh KH Hasyim Asy'ari, plays a key role in shaping the habitus of students, enabling them to accommodate differences, maintain interfaith harmony, and contribute to social harmony. The results of this study show that education based on local wisdom at Pesantren Tebuireng not only strengthens the cultural and religious identity of the students but also contributes to creating a more tolerant and harmonious society amidst diversity.Keywords: Local wisdom, Pesantren Tebuireng, habitus, Pierre Bourdieu, social harmony, tolerance, Islamic education.